The Effects of Sex and Body Weight on Renal Graft Function—The Role of CCL2 - Magdalena Nalewajska (MDPI AG, 2021)
There are reports on the effects of excessive recipient body weight on renal graft function. Increased CCL2 (chemokine CC-mortif ligand 2) production is observed in patients with excessive body weight. CCL2 also exacerbates the inflammatory process in the renal graft. A total of 49 renal graft recipients of both sexes having undergone renal biopsy within the last 18 months were retrospectively reviewed. At their most recent appointment the patients’ plasma concentrations of CCL2 were evaluated. Renal function was assessed retrospectively. CCL2 concentrations were higher in men than women (p < 0.047), while higher CCL2 levels were associated with a decrease in eGFR (estimated glomerular filtration rate) during the first year post Tx (kidney transplantation). CCL2 negatively correlated with eGFR at 5 years (R = −0.45, p < 0.040997) and positively correlated with the degree of tubular atrophy in renal biopsy specimens (R = 0.43, p < 0.027293) and with systolic pressure. Men showed significantly higher BMI (body mass index) values at the time of Tx and at their last appointment than women did (p < 0.000403; p < 0.000613, respectively). Men showed poorer long-term renal graft function, with significantly lower eGFR values at 4 and 5 years into the post-transplantation period. The male sex and excessive body weight have adverse effects on short- and long-term renal graft function, which is associated with increased levels of CCL2.